Bright Vessel Appearance on Arterial Spin Labeling MRI for Localizing Arterial Occlusion in Acute Ischemic Stroke. Issue 2 (February 2015) - Yoo, Roh-Eul; Yun, Tae Jin; Rhim, Jung Hyo; Yoon, Byung-Woo; Kang, Koung Mi; Choi, Seung Hong; Kim, Ji-Hoon; Kim, Jeong Eun; Kang, Hyun-Seung; Sohn, Chul-Ho; Han, Moon Hee
<x xml:space="preserve">Abstract</x> Background and Purpose— The purpose of this study was to evaluate whether bright vessel appearance on arterial spin labeling (ASL) MRI can help localize arterial occlusion sites in patients with acute ischemic stroke. Methods— Patients who underwent MRI for suspected acute ischemic stroke, as identified by an area of restricted diffusion, were included. All images were visually analyzed for the presence or absence of (1) arterial occlusion on time-of-flight MR angiography, (2) bright vessel appearance on ASL images, and (3) susceptibility vessel sign. McNemar 2-tailed test was used to compare the sensitivities of ASL and susceptibility-weighted imaging for the detection of arterial occlusion, using MR angiography as the reference standard. Results— ASL bright vessel appearance was significantly more common in the group with occlusion than in the group without occlusion (94% [33 of 35] versus 21% [17 of 82], respectively; P<0.001). The bright vessel appearance, when present, was seen proximal or distal to the occlusion site. The bright vessel appearance had a significantly higher sensitivity for the detection of occlusion than the susceptibility vessel sign (94% [33 of 35] versus 66% [23 of 35], respectively; P=0.002). In cases with negative MR angiography, the bright vessel appearance helped identify more additional arterial occlusions than the susceptibility vessel sign (21% [17 of 82] versus 10% [8 of 82], respectively; P=0.012). Conclusions— The bright vessel appearance on ASL imaging can provide an important diagnostic clue for the detection and localization of arterial occlusion sites in patients with acute ischemic stroke.